2021
DOI: 10.3390/ijms22052229
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Analysis of the MYB Transcription Factor Gene Family in Chili Pepper (Capsicum spp.)

Abstract: The MYB transcription factor family is very large and functionally diverse in plants, however, only a few members of this family have been reported and characterized in chili pepper (Capsicum spp.). In the present study, we performed genome-wide analyses of the MYB family in Capsicum annuum, including phylogenetic relationships, conserved domain, gene structure organization, motif protein arrangement, chromosome distribution, chemical properties predictions, RNA-seq expression, and RT-qPCR expression assays. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 84 publications
4
34
1
Order By: Relevance
“…Nevertheless, there is no comprehensive comparison of R2R3-MYBs across different pepper genomes and most of their functions are unclear. As one of the most cultivated species among the Capsicum genus, 108 and 116 C. annuum R2R3-MYBs have been genome-widely analyzed based on the Zunla 1.0 genome sequence by Wang et al (2020) and Arce-Rodríguez et al (2021), respectively. The reason for the disparity in different number of R2R3-MYBs could be that other known R2R3-MYB plant proteins were also used for identification in Arce-Rodríguez et al (2021) work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, there is no comprehensive comparison of R2R3-MYBs across different pepper genomes and most of their functions are unclear. As one of the most cultivated species among the Capsicum genus, 108 and 116 C. annuum R2R3-MYBs have been genome-widely analyzed based on the Zunla 1.0 genome sequence by Wang et al (2020) and Arce-Rodríguez et al (2021), respectively. The reason for the disparity in different number of R2R3-MYBs could be that other known R2R3-MYB plant proteins were also used for identification in Arce-Rodríguez et al (2021) work.…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most cultivated species among the Capsicum genus, 108 and 116 C. annuum R2R3-MYBs have been genome-widely analyzed based on the Zunla 1.0 genome sequence by Wang et al (2020) and Arce-Rodríguez et al (2021), respectively. The reason for the disparity in different number of R2R3-MYBs could be that other known R2R3-MYB plant proteins were also used for identification in Arce-Rodríguez et al (2021) work. The 108 CaR2R3-MYBs that Wang et al (2020) identified in C. annuum were used for further analysis in this study, together with 106 CbR2R3-MYBs and 110 CcR2R3-MYBs we identified in C. baccatum and C. chinense , respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The duplicate sequences were removed manually, and the remaining sequences were cross-checked for the presence of the MYB domain using the Conserved Domains Database (CDD) of the National Centre for Biotechnology Information (NCBI) (Lu et al, 2020) and the Simple Modular Architecture Research Tool (SMART); http://smart.embl-heidelberg.de/) database. The resultant C. chinense and C. baccatum MYB encoding genes were given acronyms according to their amino acid sequence homology with C. annuum MYB genes (Arce-Rodríguez et al, 2021). Physicochemical features, such as molecular weight, theoretical isoelectric point (pI), instability index, aliphatic index, and grand average of hydrophobicity (GRAVY) of the MYB protein sequences were estimated using ProtParam (https://web.…”
Section: Identification Of Myb Genes In Capsicum Sppmentioning
confidence: 99%
“…Myeloblastosis genes have been identified only in C. annuum (Wang et al, 2020c;Arce-Rodríguez et al, 2021), and no comprehensive study has been reported in other Capsicum species, such as C. chinense, C. baccatum, and C. frutescens. In this study, we identified MYB genes in the C. chinense, C. baccatum, and C. annuum genomes, and the analysis of their expression was performed using transcriptome data and validated by quantitative real-time (qRT) PCR in the early green (EG), mature green (MG), and breaker (Br) fruit developmental stages of highly pungent C. chinense and lowly pungent C. annuum.…”
Section: Introductionmentioning
confidence: 99%